2008
DOI: 10.1098/rspb.2008.0142
|View full text |Cite
|
Sign up to set email alerts
|

Residual force enhancement in myofibrils and sarcomeres

Abstract: Residual force enhancement has been observed following active stretch of skeletal muscles and single fibres. However, there has been intense debate whether force enhancement is a sarcomeric property, or is associated with sarcomere length instability and the associated development of non-uniformities. Here, we studied force enhancement for the first time in isolated myofibrils (nZ18) that, owing to the strict in series arrangement, allowed for evaluation of this property in individual sarcomeres (nZ79). We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
179
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(195 citation statements)
references
References 45 publications
11
179
5
Order By: Relevance
“…In addition, the passive force after deactivation of an actively stretched muscle fibre is higher than the force produced after passive stretch, or after deactivation from an isometric contraction at a corresponding length [18], further suggesting that 'passive force enhancement' is owing to recruitment of a passive element, namely titin [18]. Joumaa et al [34] measured passive force enhancement in myofibrils in which active force production was prevented by removal of troponin C. Like Labeit et al [20], they also observed a Ca 2þ -induced increase in titin-based stiffness, but the increase was too small to account for passive force enhancement. They proposed that passive force enhancement not only requires Ca 2þ influx, but also requires cross-bridge formation or active force production [34].…”
Section: Is There a Role For Titin In Active Muscle?mentioning
confidence: 99%
“…In addition, the passive force after deactivation of an actively stretched muscle fibre is higher than the force produced after passive stretch, or after deactivation from an isometric contraction at a corresponding length [18], further suggesting that 'passive force enhancement' is owing to recruitment of a passive element, namely titin [18]. Joumaa et al [34] measured passive force enhancement in myofibrils in which active force production was prevented by removal of troponin C. Like Labeit et al [20], they also observed a Ca 2þ -induced increase in titin-based stiffness, but the increase was too small to account for passive force enhancement. They proposed that passive force enhancement not only requires Ca 2þ influx, but also requires cross-bridge formation or active force production [34].…”
Section: Is There a Role For Titin In Active Muscle?mentioning
confidence: 99%
“…The force remains elevated after the stretch to reach a steady-state level that is higher than that produced during isometric contractions at corresponding lengths (8,24,38). The mechanisms responsible for this "residual force enhancement" remain elusive and there is substantial disagreement in the literature.Recent studies with isolated myofibrils, preparations in which individual sarcomeres (22,23,36,37,41,43) and half-sarcomeres in series (44, 45) can be evaluated, have shown intriguing results. Whereas a few studies suggest that force enhancement could be linked to sarcomeres and half-SL nonuniformity, as half-sarcomeres change their length continuously during activation and relaxation (36,44,45), some others show that sarcomeres may be stable (22,37), and that the increase in force after stretch are caused by contractile and/or passive structures.…”
mentioning
confidence: 99%
“…Whereas a few studies suggest that force enhancement could be linked to sarcomeres and half-SL nonuniformity, as half-sarcomeres change their length continuously during activation and relaxation (36,44,45), some others show that sarcomeres may be stable (22,37), and that the increase in force after stretch are caused by contractile and/or passive structures. Furthermore, studies that attribute the residual force enhancement to sarcomeric structures present experimental data and interpretations that are highly variable.…”
mentioning
confidence: 99%
“…10B) that remains at the end of a long (5-10 s) tetanus was originally observed on isolated whole muscles of the frog (Fenn, 1924;Abbott & Aubert, 1952;Hill & Howarth, 1959) and has later been subjected to detailed studies on isolated single muscle fibres (Edman et al, 1978Sugi, 1972;Edman & Tsuchiya, 1996, Sugi & Tsuchiya, 1988Julian & Morgan, 1979;Rassier & Herzog, 2004a, 2004b, Herzog & Rassier, 2006 and, recently, on isolated cardiac and skeletal muscle myofibrils (Telley et al, 2006;Joumaa et al, 2008;Rassier et al, 2003). The continued interest in this phenomenon is based on the fact that the longlasting force enhancement by stretch does not seem to be readily explainable on the basis of the slidingfilament hypothesis.…”
Section: Residual Force Enhancement After Stretchmentioning
confidence: 99%